2019
DOI: 10.1001/jama.2019.9059
|View full text |Cite|
|
Sign up to set email alerts
|

Psychological Consequences of Admission to the ICU

Abstract: For most patients and their families, admission to the intensive care unit (ICU) is an unanticipated event that causes substantial psychological distress. For patients, short-and longterm consequences include delirium, anxiety, depression, and acute and posttraumatic stress disorder (PTSD). 1 Psychological consequences may be exacerbated by delusions experienced during delirium, 2 which is common among critically ill patients and has adverse effects on physical and cognitive function and leads to increased hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
0
17
0
2
Order By: Relevance
“…22,34,39,44,51,71,82,88,98 Although underexplored, this medication harm has the potential to cause both unwanted physical and psychological ramifications for patients due to the distress associated with hospitalisation and intensive care stays. 115 Many studies also found a high proportion of preventable medication harm events to be caused by CV medications. 5,62,70,77,88,98 The resultant financial impact and consumption of healthcare resources due to potentially avoidable hospital presentations and prolonged length of hospital stays should also be considered when measuring the magnitude of the harm.…”
Section: Discussionmentioning
confidence: 99%
“…22,34,39,44,51,71,82,88,98 Although underexplored, this medication harm has the potential to cause both unwanted physical and psychological ramifications for patients due to the distress associated with hospitalisation and intensive care stays. 115 Many studies also found a high proportion of preventable medication harm events to be caused by CV medications. 5,62,70,77,88,98 The resultant financial impact and consumption of healthcare resources due to potentially avoidable hospital presentations and prolonged length of hospital stays should also be considered when measuring the magnitude of the harm.…”
Section: Discussionmentioning
confidence: 99%
“…The first time in the ICU can be very scary: being critically ill, not being able to breathe, having severe pain etc. These memories are recalled when waking up and can become nightmares, even delirium (Rose et al, 2019;Boehm et al, 2021). These feelings are hard to communicate vocally during the ICU stay due to the patient's need for ventilation assistance.…”
Section: Intensive Cared Patientsmentioning
confidence: 99%
“…Delirium appears with different degrees of irritability, anger, fear, anxiety, and perplexity and can be characterised as anxiety, depression, acute and post-traumatic stress (Rose et al, 2019). The delirium experience has emotional, cognitive, physical, relational, spiritual, and situational dimensions, and there are feelings and memories that often stay in the memory for a long time (Boehm et al, 2021).…”
Section: Intensive Cared Patientsmentioning
confidence: 99%
“…A internação em UTI é uma experiência geradora de angústia e sofrimento para os pacientes e familiares devido à representação desse ambiente, que envolve cuidados intensivos, alta complexidade de ações e procedimentos, impessoalidade e prognóstico incerto, causando um impacto emocional (Monteiro et al, 2017;Nunes & Gabarra, 2017). Naturalmente, esse cenário é desencadeador de situações estressoras e ansiogênicas para a família (Rose et al, 2019).…”
Section: Introductionunclassified